1994
DOI: 10.1111/j.1349-7006.1994.tb02087.x
|View full text |Cite
|
Sign up to set email alerts
|

Mortality among Inhabitants of an HTLV‐I Endemic Area in Japan

Abstract: A community‐based cohort study was conducted to clarify the risk of human T‐cell leukemia virus type I (HTLV‐I) infection for cause‐specific deaths. A total of 1,997 individuals (751 men and 1,246 women) aged 30 or older in A‐IsIand, Nagasaki Prefecture, Japan who had voluntarily attended annual mass health examinations, including serum HTLV‐I antibody test, were followed up for a mean period of 5.3 years. In a Cox proportional hazards analysis adjusted for age at baseline, the HTLV‐I seropositivity was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 28 publications
1
18
1
Order By: Relevance
“…Iwata et al [7] reported that the hazard ratio associated with HTLV-1 infection for death from all causes, excluding ATL, was 1.77 (95% CI, 0.93-3.37) for males and 1.87 (95% CI, 1.12-3.12) for females, although analysis of cause-specific mortality revealed a significantly increased risk for nonneoplastic disease in each group. Arisawa et al [2] reported that HTLV-1-seropositivity was associated with increased mortality from all causes, excluding ATL (risk ratio [RR], 1.3; 95% CI, 1.0 -1.7), and that HTLV-1 infection was not associated with an increased risk of any cancer other than ATL, colorectal cancer, liver cancer, and lung cancer but was associated with a reduced risk of gastric cancer (RR, 0.42; 95% CI, 0.17-0.99).…”
Section: Discussionmentioning
confidence: 93%
“…Iwata et al [7] reported that the hazard ratio associated with HTLV-1 infection for death from all causes, excluding ATL, was 1.77 (95% CI, 0.93-3.37) for males and 1.87 (95% CI, 1.12-3.12) for females, although analysis of cause-specific mortality revealed a significantly increased risk for nonneoplastic disease in each group. Arisawa et al [2] reported that HTLV-1-seropositivity was associated with increased mortality from all causes, excluding ATL (risk ratio [RR], 1.3; 95% CI, 1.0 -1.7), and that HTLV-1 infection was not associated with an increased risk of any cancer other than ATL, colorectal cancer, liver cancer, and lung cancer but was associated with a reduced risk of gastric cancer (RR, 0.42; 95% CI, 0.17-0.99).…”
Section: Discussionmentioning
confidence: 93%
“…12) In addition, it is noteworthy that there was a significant dose-response relationship between the antibody titer, a correlate of HTLV-I proviral load, 13,14) and mortality rate. The findings from the present study may support the idea that HTLV-I infection exerts an adverse effect on mortality which is greater than that caused only by the development of ATL.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous cohort study performed at A-Island, an HTLV-I endemic area of Nagasaki, Japan, HTLV-I seropositivity was associated with an approximately 1.8-1.9-fold increased risk of mortality, even after the effect of ATL was excluded. 12) However, the small number of deaths precluded detailed analysis of cause-specific mortality, and the generalizability of the results remained unclear.…”
mentioning
confidence: 99%
“…Several epidemiologic studies have reported the mortality rates, incidence rates and the cumulative risks of ATL among HTLV-I carriers in various countries in the world (Tajima et al, 1987;Murphy et al, 1989;Tokudome et al, 1989;Kondo et al, 1989;Iwata et al, 1994;Cleghorn et al, 1995;Gerard et al, 1995). However, most of the earlier studies on the incidence rates were based on seroprevalence data from only a small proportion of the population examined or from voluntary blood donors.…”
mentioning
confidence: 94%